2020
DOI: 10.4103/jfmpc.jfmpc_33_20
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and epilepsy: What they know, do not know, and need to know: A cross-sectional study of Taif City

Abstract: Objective: The main aim of this study was to assess schoolteachers’ knowledge of and attitudes toward epilepsy in Taif City, in the western region of Saudi Arabia. Method: A structured 28-item questionnaire was distributed to and collected from 290 schoolteachers between November 2017 and November 2018 in Taif City. Results: Generally, a negative attitude toward epilepsy was observed in this study. Of the 290 schoolteachers in this study, 80%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 37 publications
4
20
5
Order By: Relevance
“…The ability of PWE to practice daily activities, such as driving a car, has been a considerable issue globally, where the challenge is to find a balance between viability and safety exists [65] , [66] . Although it is a primary concern, a large proportion of respondents did believe in the feasibility of PWE to drive, which is greater than recently reported in Saudi Arabia [13] , [15] , [56] and consistent with a study in Taif City [41] . On the other hand, only one-third of the respondents thought that patients could participate in sporting activities.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The ability of PWE to practice daily activities, such as driving a car, has been a considerable issue globally, where the challenge is to find a balance between viability and safety exists [65] , [66] . Although it is a primary concern, a large proportion of respondents did believe in the feasibility of PWE to drive, which is greater than recently reported in Saudi Arabia [13] , [15] , [56] and consistent with a study in Taif City [41] . On the other hand, only one-third of the respondents thought that patients could participate in sporting activities.…”
Section: Discussionsupporting
confidence: 85%
“…The percentage of respondents who agreed they would marry or allow the marriage of their offspring to PWE was considerably lower than those reported in Qassim [38] , Al-Kharj [18] , Majmaah [37] , and Jeddah [15] , and developed countries, such as Austria [61] , and New Zealand [52] . However, this was higher than prior studies in Aseer [19] , Taif [41] , and other Saudi regions [13] , [36] and remained higher compared to other populations, including Greece [48] , Jordan [44] , the UAE [45] , and Egypt [62] . These contradictions could be due to the impact of local traditions, where marriage is mostly arranged and authorized by the parents.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Two studies in Tabuk and Taif found that 56.4% to 59% of the studied teachers thought it was a psychological disorder. 29 , 31 There has been a significant change in the knowledge of the cause of epilepsy over time. The majority of recent studies have shown that most teachers believe it is related to a neurological disorder.…”
Section: Teachers’ Knowledge and Attitude Toward Epilepsy In Saudi Arabia In Comparison To Other Countriesmentioning
confidence: 99%